Pectin-Tin(IV) molybdosilicate: An ecofriendly cationic exchanger and its potential for sorption of heavy metals from aqueous solutions; Resource-Efficient Technologies; Vol. 2, Suppl. 1 - Nimisha K. V. (2016, 2016)
Title screen